The role of nano-scaled structural non-uniformities on deformation twinning and stress-induced transformation in a cold rolled multifunctional β-titanium alloy. (1st March 2020) - Liang, Qianglong; Kloenne, Zachary; Zheng, Yufeng; Wang, Dong; Antonov, Stoichko; Gao, Yipeng; Hao, Yulin; Yang, Rui; Wang, Yunzhi; Fraser, Hamish L.
Abstract: The microstructure in a multifunctional β-titanium alloy, Ti–24Nb–4Zr–8Sn (wt%), before and after cold rolling was investigated using conventional and aberration-corrected scanning/transmission electron microscopy. With the presence of nano-scaled orthorhombic phase (O′) and hexagonal phase (ω), primary {332}<113>β deformation twins were activated during cold rolling with a thin layer of orthorhombic martensite (α″) occupying every twin boundary. In the interior of primary twins, nano-scaled α″ particles were observed, together with secondary {112}<111>β twins. Our work may indicate that the pre-formed nano-scaled O′ phase assists in activating the {332}<113>β deformation twining and O′ phase transforms to nano-scaled stress-induced α″ during cold rolling. Graphical abstract: Image, graphical abstract